2018
DOI: 10.23736/s1824-4785.18.03081-9
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging in adaptive radiotherapy of gastrointestinal tumors

Abstract: Overview and main research question of studies in radiation treatment planning of oesophageal cancer (Table 1), pancreas cancer (Table 2), liver cancer (Table 3), rectal cancer (Table 4), anal cancer (Table 5)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 99 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…They promise a clinical challenge for physicians, because they may have various growth patterns ranging from very slowly progressive to rapidly aggressive tumors. An effective diagnosis of NEN is based on clinical presentation, pathology, cross-sectional imaging (computed tomography (CT) or magnetic resonance imaging (MRI)), and functional nuclear medicine procedures, including 68-Gallium PET and 18FDG PET [4,5,6]. Recently, the involvement of the immune system and the role of tumor micro-environment has also been suggested as important in tumor evolution [7].…”
Section: Introductionmentioning
confidence: 99%
“…They promise a clinical challenge for physicians, because they may have various growth patterns ranging from very slowly progressive to rapidly aggressive tumors. An effective diagnosis of NEN is based on clinical presentation, pathology, cross-sectional imaging (computed tomography (CT) or magnetic resonance imaging (MRI)), and functional nuclear medicine procedures, including 68-Gallium PET and 18FDG PET [4,5,6]. Recently, the involvement of the immune system and the role of tumor micro-environment has also been suggested as important in tumor evolution [7].…”
Section: Introductionmentioning
confidence: 99%
“…18 F-FDG-PET/CT, as well as MRI, can be theoretically used for adaptive dose escalated CRT in LARC [29,30]. Moreover, some studies reported a signi cant correlation between early 18 F-FDG-PET/CT and pathological tumor response [31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Our combined approach allowed to further improved pCR but without worsening of toxicity. This has important clinical implication based on the emerging data on the possibility to avoid major surgery in LARC patients with complete clinical response after preoperative CRT [30,35].…”
Section: Discussionmentioning
confidence: 99%
“…Our combined approach allowed to further improved pCR but without worsening of toxicity. This has important clinical implication based on the emerging data on the possibility to avoid major surgery in LARC patients with complete clinical response after preoperative CRT [30,38].…”
Section: Discussionmentioning
confidence: 99%